(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
لاحظنا من خلال دراستنا أن الغازات المنطلقة من مصفاة البترول في بانياس تؤثر سلبا في الجهاز الإعاشي والتكاثري لأشجار الأوكاليبتوس والأكاسيا المجاورة للمصفاة ، ويتجلى الأذى في ضعف نمو الأشجار بسبب الاختلال الحاصل في النظام المائي والمعدني والغازي للنباتات، وفي أبعاد الثمار وحبات الطلع وحيويتها, ويتجلى الأذى بظهور بقع داكنة على الأوراق وفي المراحل المتقدمة يؤدي إلى تلف جزئي أو كامل لهذه الأوراق. We have noticed through our study that the gases emitted from petrol refinery in Banias affects negatively on the productively, and nourshing system of the Eucalyptus and Acacia trees nearby to the refinery. The injury, appears by reducing, trees grouth due to result disturbance of gaseous, mineral and water systems of plants, and regression in the dimensions of fruits and pollen and its virtality injury freshness. This injury reaches to a degree of occurance of several necrosis of leaves stages, it leads to partial or total destruction to these leaves.